(untitled) (Baghdad Science Journal, 2022)
Aleppo bentonite was investigated to remove ciprofloxacin hydrochloride from aqueous solution. Batch adsorption experiments were conducted to study the several factors affecting the removal process, including contact time, pH of solution, bentonite dosage, ion strength, and temperature. The optimum contact time, pH of solution and bentonite dosage were determined to be 60 minutes, 6 and 0.15 g/50 ml, respectively. The bentonite efficiency in removing CIP decreased from 89.9% to 53.21% with increasing Ionic strength from 0 to 500mM, and it increased from 89% to 96.9% when the temperature increased from 298 to 318 K. Kinetic studies showed that the pseudo second-order model was the best in describing the adsorption system. The adsorption equilibrium data is better represented by the Langmuir isotherm, and the maximum adsorption capacities of CIP were defined as 243.9, 270.27, 285.71 mg/g at 298, 308 and 318 K, respectively. Thermodynamic parameters were figured out showing that the adsorption was spontaneous and endothermic according to the negative values of ∆Gº and positive value of ∆Hº respectively. Based on these results, Aleppo bentonite seems to be an effective raw material for CIP adsorption and removal from aqueous solutions.